Modern views on the pharmacocorrection of disturbance of protein’s exchange (Literature review). - Ieromenko, R. F.; Ostapets, M. O.; Karabut, L. V. (Journal of Education, Health and Sport, 2017)
Stressful situations for the body, in particular acute (myocardial infarction, hepatitis B, etc.) and chronic (autoimmune, renal failure, cirrhosis, etc.) diseases of internal organs and systems of various etiologies lead to hypoproteinemia, and as a consequence - functional and organic disorders. The article analyzes modern scientific literature dates about pharmacological correction of protein metabolism disorders. It is established that despite a wide range of anabolic drugs, there is a need to search for and create a new anabolic agent with more pronounced anabolic action and a high level of safety.